Triangle ABC is right angled at B and D is the midpoint of side BC. Prove that \[A{C^2} = 4A{D^2} - 3A{B^2}\].
Answer
Verified
463.2k+ views
Hint:
Here, we will use the given information to write BD in terms of BC. Then, we will use Pythagoras’s theorem in both triangle ADB and ACB. We will simplify the equations obtained using the value of BD, and then compare the two equations to prove that \[A{C^2} = 4A{D^2} - 3A{B^2}\].
Formula Used:
We will use the formula of the Pythagoras’s theorem, \[{\rm{Hypotenuse}}{{\rm{e}}^2} = {\rm{Bas}}{{\rm{e}}^2} + {\rm{Perpendicula}}{{\rm{r}}^2}\].
Complete step by step solution:
First, we will draw the figure of the given triangle.
Here, D is the midpoint of BC and \[\angle B = 90^\circ \].
Since D is the midpoint of BC, we get
\[BD = DC\]
We can observe that \[BD + DC = BC\].
Substituting \[BD = DC\] in the equation, we get
\[ \Rightarrow BD + BD = BC\]
Adding the terms, we get
\[ \Rightarrow 2BD = BC\]
Dividing both sides by 2, we get
\[ \Rightarrow BD = \dfrac{1}{2}BC\]
Therefore, we get
\[ \Rightarrow BD = \dfrac{1}{2}BC\]
Next, we will use the Pythagoras’s theorem.
The Pythagoras’s theorem states that the square of the hypotenuse of a right angled triangle is equal to the sum of squares of the other two sides, that is \[{\rm{Hypotenuse}}{{\rm{e}}^2} = {\rm{Bas}}{{\rm{e}}^2} + {\rm{Perpendicula}}{{\rm{r}}^2}\].
Therefore, in triangle ADB, we get
\[A{D^2} = B{D^2} + A{B^2}\]
Substituting \[BD = \dfrac{1}{2}BC\] in the equation, we get
\[ \Rightarrow A{D^2} = {\left( {\dfrac{1}{2}BC} \right)^2} + A{B^2}\]
Simplifying the expression, we get
\[ \Rightarrow A{D^2} = \dfrac{1}{4}B{C^2} + A{B^2}\]
Subtracting \[A{B^2}\] from both sides of the equation, we get
\[\begin{array}{l} \Rightarrow A{D^2} - A{B^2} = \dfrac{1}{4}B{C^2} + A{B^2} - A{B^2}\\ \Rightarrow A{D^2} - A{B^2} = \dfrac{1}{4}B{C^2}\end{array}\]
Multiplying both sides of the equation by 4, we get
\[ \Rightarrow 4\left( {A{D^2} - A{B^2}} \right) = \dfrac{1}{4}B{C^2} \times 4\]
Simplifying the expression using the distributive law of multiplication, we get
\[ \Rightarrow 4A{D^2} - 4A{B^2} = B{C^2}\]
Now, using the Pythagoras’s theorem in triangle ACB, we get
\[A{C^2} = B{C^2} + A{B^2}\]
Subtracting \[A{B^2}\] from both sides, we get
\[\begin{array}{l} \Rightarrow A{C^2} - A{B^2} = B{C^2} + A{B^2} - A{B^2}\\ \Rightarrow A{C^2} - A{B^2} = B{C^2}\end{array}\]
From the equations \[A{C^2} - A{B^2} = B{C^2}\] and \[4A{D^2} - 4A{B^2} = B{C^2}\], we get
\[ \Rightarrow A{C^2} - A{B^2} = 4A{D^2} - 4A{B^2}\]
Adding \[A{B^2}\] to both sides, we get
\[ \Rightarrow A{C^2} - A{B^2} + A{B^2} = 4A{D^2} - 4A{B^2} + A{B^2}\]
Therefore, we get
\[ \Rightarrow A{C^2} = 4A{D^2} - 3A{B^2}\]
Hence, we have proved that \[A{C^2} = 4A{D^2} - 3A{B^2}\].
Note:
We have used the distributive law of multiplication to multiply 4 by \[\left( {A{D^2} - A{B^2}} \right)\]. The distributive law of multiplication states that \[a\left( {b + c} \right) = a \cdot b + a \cdot c\].
The point D is the midpoint of side BC. This means that AD bisects BC into two equal parts. Therefore, AD is a median of the given triangle ABC. A triangle is a two dimensional closed geometric shape which has 3 sides.
Here, we will use the given information to write BD in terms of BC. Then, we will use Pythagoras’s theorem in both triangle ADB and ACB. We will simplify the equations obtained using the value of BD, and then compare the two equations to prove that \[A{C^2} = 4A{D^2} - 3A{B^2}\].
Formula Used:
We will use the formula of the Pythagoras’s theorem, \[{\rm{Hypotenuse}}{{\rm{e}}^2} = {\rm{Bas}}{{\rm{e}}^2} + {\rm{Perpendicula}}{{\rm{r}}^2}\].
Complete step by step solution:
First, we will draw the figure of the given triangle.
Here, D is the midpoint of BC and \[\angle B = 90^\circ \].
Since D is the midpoint of BC, we get
\[BD = DC\]
We can observe that \[BD + DC = BC\].
Substituting \[BD = DC\] in the equation, we get
\[ \Rightarrow BD + BD = BC\]
Adding the terms, we get
\[ \Rightarrow 2BD = BC\]
Dividing both sides by 2, we get
\[ \Rightarrow BD = \dfrac{1}{2}BC\]
Therefore, we get
\[ \Rightarrow BD = \dfrac{1}{2}BC\]
Next, we will use the Pythagoras’s theorem.
The Pythagoras’s theorem states that the square of the hypotenuse of a right angled triangle is equal to the sum of squares of the other two sides, that is \[{\rm{Hypotenuse}}{{\rm{e}}^2} = {\rm{Bas}}{{\rm{e}}^2} + {\rm{Perpendicula}}{{\rm{r}}^2}\].
Therefore, in triangle ADB, we get
\[A{D^2} = B{D^2} + A{B^2}\]
Substituting \[BD = \dfrac{1}{2}BC\] in the equation, we get
\[ \Rightarrow A{D^2} = {\left( {\dfrac{1}{2}BC} \right)^2} + A{B^2}\]
Simplifying the expression, we get
\[ \Rightarrow A{D^2} = \dfrac{1}{4}B{C^2} + A{B^2}\]
Subtracting \[A{B^2}\] from both sides of the equation, we get
\[\begin{array}{l} \Rightarrow A{D^2} - A{B^2} = \dfrac{1}{4}B{C^2} + A{B^2} - A{B^2}\\ \Rightarrow A{D^2} - A{B^2} = \dfrac{1}{4}B{C^2}\end{array}\]
Multiplying both sides of the equation by 4, we get
\[ \Rightarrow 4\left( {A{D^2} - A{B^2}} \right) = \dfrac{1}{4}B{C^2} \times 4\]
Simplifying the expression using the distributive law of multiplication, we get
\[ \Rightarrow 4A{D^2} - 4A{B^2} = B{C^2}\]
Now, using the Pythagoras’s theorem in triangle ACB, we get
\[A{C^2} = B{C^2} + A{B^2}\]
Subtracting \[A{B^2}\] from both sides, we get
\[\begin{array}{l} \Rightarrow A{C^2} - A{B^2} = B{C^2} + A{B^2} - A{B^2}\\ \Rightarrow A{C^2} - A{B^2} = B{C^2}\end{array}\]
From the equations \[A{C^2} - A{B^2} = B{C^2}\] and \[4A{D^2} - 4A{B^2} = B{C^2}\], we get
\[ \Rightarrow A{C^2} - A{B^2} = 4A{D^2} - 4A{B^2}\]
Adding \[A{B^2}\] to both sides, we get
\[ \Rightarrow A{C^2} - A{B^2} + A{B^2} = 4A{D^2} - 4A{B^2} + A{B^2}\]
Therefore, we get
\[ \Rightarrow A{C^2} = 4A{D^2} - 3A{B^2}\]
Hence, we have proved that \[A{C^2} = 4A{D^2} - 3A{B^2}\].
Note:
We have used the distributive law of multiplication to multiply 4 by \[\left( {A{D^2} - A{B^2}} \right)\]. The distributive law of multiplication states that \[a\left( {b + c} \right) = a \cdot b + a \cdot c\].
The point D is the midpoint of side BC. This means that AD bisects BC into two equal parts. Therefore, AD is a median of the given triangle ABC. A triangle is a two dimensional closed geometric shape which has 3 sides.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE